2015
DOI: 10.1542/neo.16-7-e406
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Saturation Targeting by Automatic Control of Inspired Oxygen in Premature Infants

Abstract: Maintenance of oxygen saturation targets and avoidance of extreme high and low levels of oxygenation in premature infants are difficult because of their respiratory instability and staff time limitations. Automated control of inspired oxygen is being proposed as a strategy to improve oxygenation targeting in these infants. This article presents the factors that affect oxygenation targeting, describes the systems for closed-loop control of oxygen, and discusses the evidence on their efficacy and limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The previous studies have shown some risks related to development of mechanized control systems in oxygen therapy for respiratory complicated patients (1,3,5). Therefore, a system was designed and implemented that could easily and promptly warn nurses based on patients' condition.…”
Section: Strengths Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies have shown some risks related to development of mechanized control systems in oxygen therapy for respiratory complicated patients (1,3,5). Therefore, a system was designed and implemented that could easily and promptly warn nurses based on patients' condition.…”
Section: Strengths Of Studymentioning
confidence: 99%
“…On the other hand, hyperoxemia in some cases may lead heart, lungs, brain, retina and hearing system damages. Maintenance of adequate blood oxygen concentration to minimize the risks of both hypoxemia and hyperoxemia are the main goal related mechanical ventilation in hospitalized premature infants (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hyperoxemia in some cases may lead to heart, lungs, brain, retina and hearing system damages. Maintenance of adequate blood oxygen concentration to minimize the risks of both hypoxemia and hyperoxemia are the main goal related to mechanical ventilation in hospitalized premature infants (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%